Congenital Maxillomandibular Fusion: A Rare Case of Isolated True Bony Syngnathia - Aguiling, Patrick O.; King-Chao, Nikki Lorraine Y.; Veloro, Lyra V. (Philippine Journal of Otolaryngology Head and Neck Surgery, 2018)
Objective: To present a rare case of congenital maxillomandibular fusion or syngnathia. Methods: Study Design: Case report Setting: Tertiary Private Teaching Hospital Patient: One Results: A 3-year-old girl with oral adhesion (syngnathia) caused by a mandibular to maxillary fibrous band underwent successful surgical division of maxillomandibular bony fusion. Subsequent monitoring and serial oral dilations were performed post operatively, resulting in mouth opening of 24mm over a period of 3 months. Currently, the patient is able to tolerate a general liquid diet. Conclusion: Congenital maxillomandibular fusion is a very rare condition with few cases reported. We hope this report contributes to its diagnosis and management in other children. Keywords: Congenital maxillomandibular fusion, syngnathia